The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.system.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Individual factors and successful learning in a hybrid course

Abstract: What personality factors make for a successful hybrid L2 learning experience? While previous studies have examined online learning in comparative terms (i.e. Which format is better: in class or hybrid?), this study examines certain personality and cognitive factors that might define the ideal hybrid language learner. All informants studied introductory Spanish with multimedia materials supported by synchronous chat (video, voice, text). Personality and cognitive traits were probed using the Big Five Inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…Being able to record a conversation multiple times or rehearse and stage a role-play and send the best version to the instructor allowed the shyer and weaker of my students to feel in charge of their oral abilities. This seems to confirm Arispe and Blake's (2012) findings that low-verbal learners profit from hybrid instruction because they need more time for individual language study and practice, enjoy control over the pace of their learning, and are simply too "overwhelmed by fast-talking native or near-native instructors who are trying to model real-life speech" (p. 459). Such students do well online where the pace of practice is under their control and where they can practice a task until it conforms to instructor expectations.…”
Section: Curriculum and Delivery Formatsupporting
confidence: 64%
See 2 more Smart Citations
“…Being able to record a conversation multiple times or rehearse and stage a role-play and send the best version to the instructor allowed the shyer and weaker of my students to feel in charge of their oral abilities. This seems to confirm Arispe and Blake's (2012) findings that low-verbal learners profit from hybrid instruction because they need more time for individual language study and practice, enjoy control over the pace of their learning, and are simply too "overwhelmed by fast-talking native or near-native instructors who are trying to model real-life speech" (p. 459). Such students do well online where the pace of practice is under their control and where they can practice a task until it conforms to instructor expectations.…”
Section: Curriculum and Delivery Formatsupporting
confidence: 64%
“…It has become accepted wisdom that hybrid instruction is not suitable for every student (Goertler et al, 2012;Arispe & Blake, 2012;Lin, 2009;Blake et al, 2008;Winke et al 2010). The format is best suited for independent and conscientious learners (Arispe & Blake 2012) and requires a level of technology that many of today's students do not yet possess despite their familiarity with Facebook and Twitter (Goertler et al, 2012). It has also been shown that students choose courses for convenience and flexibility, and might chose a hybrid course under the mistaken impression that it is less work (Blake et al, 2008).…”
Section: Managing Student Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses in the CG had higher performance according to the association of age and the training time, considereing <30 years of age statistically significant (p 0.03), and training time lower than three years (p 0.01), inferring that DL courses may not be the best option for recent college graduates, especially when knowledge in the area is incipient or there is a lack in autonomous learning, since this characteristic determines the outcome of the learning process [13].…”
Section: Discussionmentioning
confidence: 99%
“…; Scida and Saury ; Blake and Delforge ; Blake, Wilson, Cetto, and Pardo‐Ballester ). Arispe and Blake () have noted that language learning online is often limited to beginner‐level learners, and thus a gap exists in the existing literature on this topic. Blake and Delforge () also discuss the need for further research examining language courses that are conducted fully online.…”
Section: Introductionmentioning
confidence: 99%